Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2018)
Following two special issues of the journal, one dedicated to emotions in second language learning and the other to language learning strategies, the present issue of Studies in Second Language Learning and Teaching is a regular one, bringing together six empirical studies dealing with different aspects of learning and using second and foreign languages (L2).